Trauma, archetype, and growth: A comparative psychological analysis of the ‘Killing of the wise old man’ motif in speculative fiction - Lu, Yahui; M. M., Raihanah (Environment and Social Psychology, 2025)
This study utilizes a psychological research framework to investigate the extent to which the traumatic rupture in the mentor-protagonist relationship enables posttraumatic development in speculative fiction. We examine the “killing of the wise old man” motif in Liu Cixin’s The Three-Body Problem and Ntsika Kota’s and the Earth Drank Deep using Jungian theory and Calhoun & Tedeschi’s Posttraumatic Growth (PTG) model. The protagonists’ voyages from separation, which is characterized by a psychospiritual crisis, to initiation, where cognitive dissonance and emotional turmoil induce a change in beliefs, are traced through qualitative narrative coding. Disillusionment and subsequent identity reconstruction are the outcomes of the symbolic ‘filial violence” against the mentor figure, which induces a psychic rupture that challenges fundamental values. PTG is facilitated by coping strategies, including self-disclosure, creative expression, and the revision of cultural schemas. This results in a redefined life purpose, increased resilience, and enhanced meaning-making. Our results emphasize the Antihero’s Journey as a paradigm that is effective in elucidating the manner in which literature depicts adaptive transformation in the aftermath of tragedy. This research contributes to the disciplines of trauma studies and narrative psychology by emphasizing the relationship between personal growth and archetypal disruption. It illustrates that speculative fiction is a valuable instrument for investigating psychological resilience and the processes of meaning-making in the presence of adversity.